UPAYA MENDIDIK ANAK MELALUI PERMAINAN EDUKATIF - Khobir, Abdul (IAIN Pekalongan, 2009)
﻿Game is one form of social activity that is very dominant in the early days of children. Therefore, children spend more time outside the house to play with his friends than be involved with other activities. Therefore, games for children is a form of fun activity undertaken solely for the activity itself, not because they want to get a result from such activities. This is due to children that the process of doing something is more interesting than the results that will be received. For every child, especially young children, playing means learning. Indeed the world of children is playing, since by playing, children will learn many things about everyday life. With games, we as parents can incorporate elements of education therein.